PENGARUH PELATIHAN, MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KOMPETENSI DOSEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Rahmawati putri (2022)
This study is a quantitative study that aims to determine the effect of training, work motivation and organizational culture on the competence of lecturers at the Faculty of Economics and Business, Universitas Pembangunan Nasional Veterans Jakarta. The population in this study were 110 permanent lecturers at the Faculty of Economics and Business, Universitas Pembangunan Nasional Veterans Jakarta. The selection of permanent lecturers is done randomly after determining the number of samples that can be accepted, namely 86 respondents from the total number of permanent lecturers in the Faculty of Economics and Business, Universitas Pembangunan Nasional Veterans Jakarta using random sampling. Hypothesis testing in this study used descriptive analysis and inferential analysis using the SMARTPLS 3.0 statistical test tool. While the hypothesis test was carried out by t-test and f-test using a significance level of 5% (0.05). The results of this test indicate that (1) training has a positive and significant effect on lecturer competence; (2) work motivation has a positive and insignificant effect on lecturer competence; (3) Organizational culture has a positive and significant effect on lecturer competence; (4) Training, work motivation and organizational culture simultaneously affect the competence of lecturers.